Efficacy of TNFα blockers in patients with ankylosing spondylitis and non-radiographic axial spondyloarthritis: a meta-analysis. Issue 6 (9th April 2014) - Callhoff, Johanna; Sieper, Joachim; Weiß, Anja; Zink, Angela; Listing, Joachim
Abstract : Objectives: This meta-analysis investigates the efficacy of tumour necrosis factor α (TNFα) blockers versus placebo for the treatment of ankylosing spondylitis (AS) and non-radiographic axial spondyloarthritis (nr-axSpA). Methods: A systematic literature search was conducted independently by two reviewers. Double-blind randomised controlled trials (RCTs) investigating the efficacy of adalimumab, certolizumab, etanercept, golimumab or infliximab in approved dosages in comparison with placebo were included. The use of concomitant non-steroidal antirheumatic drugs was allowed. The outcome parameters were improvement in disease activity and function measured by the Bath AS disease activity index (BASDAI), Bath AS functional index (BASFI) and ASAS40 response. The effect sizes of the changes in BASDAI/BASFI between TNFα blocker and placebo comparator groups were calculated. Mixed effect models were applied separately for RCTs with AS and nr-axSpA patients and differences between those groups were evaluated in a joint model. Results: 20 studies with data from 3096 patients were included in the analysis: 15 studies with AS patients, four with nr-axSpA patients and one with both. For AS patients, TNFα blockers showed better efficacy than placebo for BASDAI (effect size 1.00), BASFI (effect size 0.67) and ASAS40 response (OR 4.7). For nr-axSpA patients, the differences were smaller (effect sizes 0.73, 0.57; OR 3.6). However, after adjustment for the year of publication as a proxy for disease severity, no differences in the effect sizes between the AS and nr-axSpA trials were observed. Conclusions: Compared with placebo, TNFα blockers improve disease activity and functional capacity clinically meaningful for both AS and nr-axSpA patients.